Produtividade e componentes de produção do milho fertilizado com diferentes fontes e doses de zn e disponibilidade dos metais pesados tóxicos Cd, Pb e Cr - Nacke, Herbert (2011)
The objective of this study it was evaluate the effect of different sources and doses of Zn applied in corn on productivity, yield components and the availability of toxic heavy metals cadmium (Cd), lead (Pb) and chromium (Cr) for maize plants and soil cultivation. This way, eight sources were evaluated at four Zn levels in a Rhodic Eutrudox in the western region of Paraná. The results showed significant differences among the sources and levels in the availability of Zn for plants, and among the doses for productivity. For yield components the treatments had no effect. We also obtained, there was no accumulation of Cd, Pb and Cr in corn grains, and Cd and Cr in the leaf tissue of plants, however there was accumulation of Pb in the leaf tissue, showing their availability through the sources of Zn and consequent plant uptake. For the soil, it was found that the sources made available Cd, Pb and Cr, with increase proportional to the increase of the Zn doses. It was concluded that, under the experiment conditions, the fertilization with Zn provides increase of the income for the maize crop, however, doses greater than 4.0 kg ha-1 are not justified. As for the availability of toxic heavy metals Cd, Pb and Cr it was concluded that the fertilization with Zn, provided increase in the amount of toxic heavy metals Cd, Pb and Cr in the experimental soil